The “Morals of Genealogy”: Liberal Settler Colonialism, the Nova Scotia Archives, and the North American Ancestor-Hunters, 1890-1980 - McKay, Ian (Acadiensis, 2019)
Genealogy loomed large in the culture of Nova Scotia from the 1890s to the 1970s, yet when D.C. Harvey, the provincial archivist after 1931, defined the key purposes of the Public Archives of Nova Scotia, he excluded genealogical research from the core objectives of this “historical laboratory.” He was fighting a losing battle. Like it or not, the institution he headed operated as part of a transnational mnemonic network within which genealogical approaches were becoming more influential and within a province whose White colonial elite had deep connections with New England – the epicentre of popular genealogy in the United States.